Coronary Artery Calcium, Brain function and structure: the AGES-Reykjavik Study - Vidal, Jean-Sébastien (2010)
BACKGROUND AND PURPOSE: Several cardiovascular risk factors are associated with cognitive disorders in older persons. Little is known about the association of the burden of coronary atherosclerosis with brain structure and function. METHODS: Cross-sectional analysis of data from the AGES Reykjavik Study cohort of men and women born 1907-35. Coronary artery calcification (CAC), a marker of atherosclerotic burden was measured with computed tomography. Memory, speed of processing, and executive function composites were calculated from a cognitive test battery. Dementia was assessed in a multi-step procedure and diagnosed according to international guidelines. Quantitative data on total intracranial and tissue volumes [total, Gray (GMV), White (WMV), and White Matter Lesions (WMLV)], cerebral infarcts and cerebral microbleeds (CMB) were obtained with brain MRI. The association of CAC with dementia (n=165 cases) and cognitive function in non-demented subjects (n=4085), and separately with MRI outcomes, was examined in multivariate models adjusting for demographic and vascular risk factors. Analyses tested whether brain structure mediated the associations of CAC to cognitive function. RESULTS: Subjects with higher CAC were more likely to have dementia and lower cognitive scores, more likely to have lower WMV, GMV and total brain tissue, and more cerebral infarcts, CMB and WMLV. The relations of cognitive performance and dementia to CAC were significantly attenuated when the models were adjusted for brain lesions and volumes. CONCLUSIONS: In a population-based sample increasing atherosclerotic load, assessed by CAC, is associated with poorer cognitive performance and dementia, and these relations are mediated by evidence of brain pathology.